Child care consultations held by nurses within the Family Health Strategy - Oliveira, Francisco Fagner Sousa (2013)
The study aimed at identifying initiatives taken by nurses during child care routine visits in Family Health Units. It is an observational, descriptive and quantitative research. Data collection took place from August to October 2011, through the observation of three consultations carried out by eight nurses (24 appointments) for the Family Health Strategy Scheme in Picos - Piauí. During consultations, the following issues were more frequently observed:  anthropometry, reflexes according to age, encouraging of exclusive breastfeeding and advice on child hygiene. The need for further nurse training through continuous education was verified, seeking to improve care in order to contribute to the improvement of nursing care quality focused on promoting child health thru childcare consultations.